2012
DOI: 10.1007/s10973-012-2446-8
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of polymethylvinylborosiloxanes

Abstract: New branched polymethylvinylborosiloxanes (PMVBSs) with random structures were prepared, and their chemical structures were studied by spectroscopic methods (FTIR, 1 H-, 29 Si-, and 11 B-NMR) and elemental analysis (% C, % H, % Si, and % B). Average molecular weights M w and M n were determined by a size exclusion chromatography (SEC), and dynamic viscosities were measured in Brookfield cone-plate reoviscometer HBDV-II?cP. Thermal properties of PMVBSs were studied under air and under nitrogen atmosphere. Therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…A strong peak at 0.17 ppm corresponded to hydrogens in Si―CH 3 . Strong peaks at 5.83 (q, J 1 = 23.3 Hz, J 2 = 11.3Hz, 1H) and 6.02 ppm (m, J 1 = 23.3 Hz, J 2 = 11.3Hz, J 3 = 2.1Hz, 2H) corresponded to hydrogens in Si―CH═CH 2 groups . A weak peak at 2.09 ppm corresponded to hydrogen in B―OH groups .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A strong peak at 0.17 ppm corresponded to hydrogens in Si―CH 3 . Strong peaks at 5.83 (q, J 1 = 23.3 Hz, J 2 = 11.3Hz, 1H) and 6.02 ppm (m, J 1 = 23.3 Hz, J 2 = 11.3Hz, J 3 = 2.1Hz, 2H) corresponded to hydrogens in Si―CH═CH 2 groups . A weak peak at 2.09 ppm corresponded to hydrogen in B―OH groups .…”
Section: Resultsmentioning
confidence: 99%
“…This observation indicated that most silicon atoms were connected through ―O―B linkages at both sides. Moreover, a medium peak at −34.60 ppm may correspond to the middle silicon in the Si―O―Si―O―Si linkages, as shown in Fig. (c, structure (c)), which were formed from the reaction between CH 3 O―Si― and HO―Si groups.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations